2020
DOI: 10.1186/s12876-020-01211-4
|View full text |Cite
|
Sign up to set email alerts
|

An internal hernia caused by Meckel’s diverticulum: a case report

Abstract: Background: Meckel's diverticulum is a remnant of the omphalomesenteric duct. It can lead to intestinal perforation, obstruction and gastrointestinal bleeding. While the internal hernia caused by Meckel's diverticulum is rarely reported. Case presentation: We report a case of a 45-year old female patient who presented with intestinal obstruction and on laparotomy was found to have Meckel's diverticulum with internal hernia causing intestinal gangrene. Segmental bowel resection was performed and the patient had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…We assumed that the following reasons accounted for the development of small bowel volvulus secondary to Meckel’s diverticulum in our patient: First, the fibrous band that is formed from the incomplete degeneration of the omphalomesenteric duct connected to the abdominal wall or the adjacent mesentery. This fibrous band may suddenly result in abdominal internal hernia 17 or axial torsion of Meckel’s diverticulum. 18 Second, the patient had a giant Meckel’s diverticulum.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that the following reasons accounted for the development of small bowel volvulus secondary to Meckel’s diverticulum in our patient: First, the fibrous band that is formed from the incomplete degeneration of the omphalomesenteric duct connected to the abdominal wall or the adjacent mesentery. This fibrous band may suddenly result in abdominal internal hernia 17 or axial torsion of Meckel’s diverticulum. 18 Second, the patient had a giant Meckel’s diverticulum.…”
Section: Discussionmentioning
confidence: 99%
“…Meckel's diverticulum causing internal hernia and small bowel obstruction is an extremely rare complication, and it should be considered in patients with obstructive symptoms, especially in younger people without previous abdominal surgery. Haskaraca reported a case of a 45-year old female patient who presented with intestinal obstruction and at laparotomy was found to have Meckel's diverticulum with internal hernia causing intestinal gangrene (5). Other causes of internal herniation are due to adhesion of the inflamed tip of Meckel's diverticulum to the corresponding base of mesentery, through mesodiverticular band and fibrous cord extending up to umbilical wall.…”
Section: Discussionmentioning
confidence: 99%
“…It is a true diverticulum and is one of the most common digestive tract congenital abnormalities that occurs in about 2% of the population. In most cases, Meckel’s diverticulum remains asymptomatic but 4% of patients can develop complications such as diverticulitis, gastrointestinal bleeding, perforation, or intestinal obstruction [ 2 ]. Zhang et al suggested several reasons for the development of complications such as intestinal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al suggested several reasons for the development of complications such as intestinal obstruction. One possibility is that repeated inflammation can lead to the formation of adhesion bands which can cause adhesive obstruction [ 2 ]. Symptomatic or complicated Meckel’s diverticulum may therefore require surgical intervention as it is often the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%